Evaluation of pH-sensitive poly(2-hydroxyethyl methacrylate-co-2-(diisopropylamino)ethyl methacrylate) copolymers as drug delivery systems for potential applications in ophthalmic therapies/ocular delivery of drugs - P. A. Faccia; F. M. Pardini; J. I. Amalvy (eXPRESS Polymer Letters)
Smart polymers like pH sensitive systems can improve different pharmacological treatment. In this work the behavior of copolymers containing 2-hydroxyethyl methacrylate (HEMA) with different proportions of 2-(diisopropylamino) ethyl methacrylate (DPA) and different amounts of cross-linker agent, ethylene glycol dimethacrylate (EGDMA) are evaluated as pH-sensitive drug delivery systems for potential application in ophthalmic therapies. A detailed characterization of the pH-responsive behavior was performed by swelling studies and scanning electron microscopy (SEM) analysis. Drug loading and release studies at different pH values were evaluated using Rhodamine 6G (Rh6G) as a model drug. The interaction between Rh6G and hydrogels was studied by Fourier Transform Infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results show that the presence of DPA in the copolymers confers pH-responsive properties to the polymer, as noted in swelling and SEM studies, when the pH decreases below 7.40 the swelling degree increases and a porous morphology is observed. The apparent pKa of copolymers was estimated between 6.80 and 7.17 depending on the composition. The amount of Rh6G loaded depends mainly on the medium pH and the interaction between the drug and the copolymers, observed by SEM and FTIR spectrum. The release of Rh6G of copolymers p(HEMA/DPA) show a normal Fickian or anomalous diffusion behavior at different pH values, depending on the HEMA/DPA ratio.